La tutela judicial efectiva es de todos los sujetos procesales - Zúñiga Astudillo, César Andrés (2022)
The present investigation, entitled "Effective judicial protection belongs to all procedural subjects" had the objective of analyzing and studying the scope of effective judicial protection, being the response to the reparation of the rights of the procedural subjects that have not been able to access in a timely, impartial and clear way to the rights and principles that make up the Constitution of the Republic of Ecuador. Over time, effective judicial protection has become the watchful shadow of the rights and principles enshrined in our Magna Carta. Effective judicial protection is enshrined as a fundamental right and a procedural principle since it is linked to access to justice, and it is the parties to the proceedings through their sponsors who will make use of the legal remedies offered by the State to guarantee the protection of their rights. Establishing its scope of application, the General Organic Code of Proceedings, following its entry into force, states in Article 30 who are entitled to consider themselves as parties to the proceedings and to make the relevant legal requests to the court or judge.......